Studies on Industrial-Scale Thermal Modification of Wood - Dagbro, Ola (Luleå tekniska universitet, Träteknologi, 2016)
Wood as a raw material is useful for many purposes even though some properties are less than optimal, for example, dimensional stability and durability. These characteristics can however be improved by different treatment methods. Environmental awareness has led to an increased demand for environmentally friendly processes like thermal modification that does not add any chemicals to the wood in contrast to, for example, CCA-impregnated wood.This thesis mainly focuses on thermally modified wood from species such as pine, spruce and birch. The thesis present studies of physical attributes such as color, and chemical analysis of water-soluble compounds and degradation products. Treatment intensity is compared between two different industrial processes referred as Thermowood and WTT, which use respectively superheated steam and pressurized steam as heating media.Thermal modification processes darken the color of wood throughout its cross-section. The formation of darker color is related to a degradation processes that takes place during thermal modification. During thermal modification wood is exposed to temperatures between 160 - 220°C, and the temperature causes physical and chemical transformations that change some of the wood properties. Dimensional stability and durability are typically improved, but mechanical strength properties are usually negatively affected by the treatment.The studied wood species were Scots pine (Pinus sylvestris L.), Norway spruce (Picea abies L.) and Birch (Betula pendula L.). Treatments using pressurized steam were carried out under temperatures of 160°C, 170°C and 180°C, and treatments using superheated steam at normal air pressure were carried out at temperatures of 190°C and 212°C. Results showed that similar L* (lightness) can be reached at lower temperatures using pressurized steam compared to superheated steam. The residual moisture content after completed thermal modification was approximately 10% higher in wood treated with the pressurized steam process. It was found that despite an approximately 25°C lower treatment temperature, birch modified in pressurized steam was more acidic compared to birch modified in superheated steam. This will likely have further consequences, requiring more research concerning surface treatment and fixation.The thesis also includes the development of an industrial-quality control procedure based on nondestructive color measurements verified in industrial environment. Treatment intensity in industry is today certified by inspection of documented process schedule and measuring the temperature and time of the process. Quality control in this context refers to the measurement of wood color as an indirect measure of treatment intensity. The color in our study was measured using L*C*H color space. The study shows that it is possible for quality control purposes to measure the color of thermally modified wood from the surfaces of planed boards instead of sawdust or board cross sections that have been used in other studies.The thesis has a final section about academia-industry collaboration that describes how trust building was established through a fruitful relationship involving academia and regional wood products industry in northern Sweden. The study presents an example of a successful research and development alliance between university and a group of small- and medium-sized enterprises (SMEs). This alliance has been a great example on international collaboration involving researchers originating from Finland, China, Bangladesh, Spain, Russia and Sweden. Through an in-depth multi-year study of how the research cooperation developed, the paper describes how the involved companies successfully entered into a new segment of the market. === För godkännande; 2016; 20160314 (olahof); Nedanstående person kommer att disputera för avläggande av teknologie doktorsexamen. Namn: Ola Dagbro Ämne: Träfysik/Wood Physics Avhandling: Studies on Industrial-Scale Thermal Modification of Wood Opponent: Associate Professor Lidia Gurau, Faculty of Wood Engineering, Transilvania University, Brasov, Romania. Ordförande: Professor Diego Elustondo, Avd för träteknologi, Institutionen för teknikvetenskap och matematik, Luleå tekniska universitet, Luleå. Tid: Torsdag 16 juni, 2016 kl 10.00 Plats: Luleå tekniska universitet, Campus Skellefteå